The Use of Contextual Media for Elementary School English Class - 'Aqiilah, Salsabil; Maula, Qurrotu Inayatil (Literasi Nusantara, 2024)
The use of contextual-based learning media is expected to enhance student engagement in the learning process, especially in English language learning at elementary schools. This research was conducted to analyze the use of contextual-based learning media in English language learning at one of the elementary schools in Bangkalan. The research method used is descriptive qualitative, obtained from the interview, observation, and documentation from teacher and students. The research findings indicate that the school uses learning media in the form of flashcards and PowerPoint in English language subjects. The use of this learning media has been contextual by combining lesson materials with concrete examples in real life. These media are effective in enhancing students’ enthusiasm, engagement, activity, and understanding of English lesson material.